2019
DOI: 10.1002/cam4.1977
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of mast cell and microvascular densities in malignant peripheral nerve sheath tumor with and without neurofibromatosis type 1

Abstract: Malignant peripheral nerve sheath tumors (MPNSTs) are rare and aggressive soft tissue sarcomas with a significant susceptibility to metastasize early in their course. Pathogenesis is yet to be fully elucidated. Recently, the essential role of mast cells in the tumor onset of neurofibromatosis type 1 (NF1)‐associated neurofibromas and MPNSTs was confirmed in both experimental and human studies. In this study, we investigate mast cell density (MCD), microvascular density (MVD), and proliferation index (Ki‐67) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Targeting vascular pathways in MPNSTs may be beneficial, but unfortunately few studies have focused on this. Studies included in this review also showed that increased vascularity, as evidenced by increased microvascular density as well as increased expression of VEGF, may be associated with more aggressive biological behavior ( 57 , 59 ). It seems that many other targets may be of prognostic value as well emphasizing the need for further research into MPNST tumor biology.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Targeting vascular pathways in MPNSTs may be beneficial, but unfortunately few studies have focused on this. Studies included in this review also showed that increased vascularity, as evidenced by increased microvascular density as well as increased expression of VEGF, may be associated with more aggressive biological behavior ( 57 , 59 ). It seems that many other targets may be of prognostic value as well emphasizing the need for further research into MPNST tumor biology.…”
Section: Discussionmentioning
confidence: 84%
“…High MVD was associated with worse survival in one/four studies. This association was also significant in multivariable analyses (HR 7.3, 95% CI: 1.4–38.5) ( 57 ). High VEGF staining was associated with worse survival in one/two studies, but this was not studied in a multivariable model ( 59 ).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…However, drastically reducing the number of mast cells does not impair mouse neurofibroma development [66], and therapeutic strategies targeting mast cells in MPNST patients largely failed [67]. A trend toward a lower mast cell count in MPNST [68,69] has been challenged [44]. Thus, the functional role of mast cells in the neurofibroma to MPNST sequence may be marginal.…”
Section: Tumor Microenvironmentmentioning
confidence: 99%